Late-time Observations of GRB 080319B: Jet Break, Host Galaxy, and Accompanying Supernova - Tanvir, N.; Rol, E.; Levan, A.; Svensson, K.; Fruchter, A.; Granot, J.; O’Brien, P.; Wiersema, K.; Starling, R.; Jakobsson, P.; Fynbo, J.; Hjorth, J.; et al. (Institute of Physics Publishing, Inc., 2010)
The Swift-discovered GRB 080319B was by far the most distant source ever observed at naked-eye brightness,reaching a peak apparent magnitude of 5.3 at a redshift of z = 0.937. We present our late-time optical (HubbleSpace Telescope, Gemini, and Very Large Telescope) and X-ray (Chandra) observations, which confirm that anachromatic break occurred in the power-law afterglow light curve at~ 11 days post-burst. This most likely indicatesthat the gamma-ray burst (GRB) outflow was collimated, which for a uniform jet would imply a total energy inthe jet Ejet 1052 erg. Our observations also show a late-time excess of red light, which is well explained ifthe GRB was accompanied by a supernova (SN), similar to those seen in some other long-duration GRBs. Thelatest observations are dominated by light from the host and show that the GRB took place in a faint dwarf galaxy(r(AB) ˜ 27.0, rest frame MB ˜ -17.2). This galaxy is small even by the standards of other GRB hosts, whichis suggestive of a low-metallicity environment. Intriguingly, the properties of this extreme event—a small hostand bright SN—are entirely typical of the very low luminosity bursts such as GRB 980425 and GRB 060218.